Grammatical Problems in the Methodology Section of Master Theses - Mawarni, Mawarni; Yunita, Wisma; Sujarwati, Iis (EDULIA: English Education, Linguistic and Art Journal, 2024)
The methodology section is one of the most important aspects of a master thesis because it describes how the research was done and what method and procedure was taken in that research. This research aimed to discover the most common grammatical problems and possible causes of grammatical issues in master theses written by English education postgraduate program students at Bengkulu University, especially in the methodology section. This study used a mixed method, namely qualitative and quantitative. Most of the grammatical problems were investigated quantitatively, and the causes of grammatical problems were studied qualitatively. The corpus of this study was 20 master theses written by English education postgraduate program students who graduated in 2021. The findings showed that the most frequent grammatical problems found in the methodology section of the master theses were incorrect verbs, 38,60% or 44 times, which were dominated by tense confusion and subject-verb agreement, which confused the reader. Further, they also often lack the necessary syntactic connections between the verb and the nearest subject. The cause of the grammatical problems found in the methodology section of the theses was carelessness, first language interference, and translation. Carelessness becomes the highest possible cause of the grammatical problems committed by students. The conclusion of this research provides information about the most frequent grammatical problems and possible causes in the master theses of methodology section. Keywords: Grammatical Problems, Methodology Section, Writing Theses.